43 Frontal plane knee and pelvis angles during single leg squat and step down tasks do not differ between people with and without chronic ankle instability. (12th October 2015) - Smith, MD; Russell, T; Thomson, A; MacIntyre, E; Devane, H; Howe, E; Tucker, K
Abstract : Background: Differences in sagittal plane lower limb kinematics have been identified in people with chronic ankle instability (CAI) during sporting activites; however, studies have not considered frontal plane kinematics or assessment of kinematics during functional tasks. Objective: To determine if frontal plane kinematics differ in people with and without CAI during single leg squat and step down tasks. Design: Case-control study. Setting: Research laboratory. Participants: Eighteen individuals with CAI (22.5 ± 2 years) and 18 individuals with no previous ankle injury (23.5 ± 4 years) were recruited. Participants with CAI had at least one previous ankle sprain and a minimum of one of the following: repeated sprains on the same ankle, "giving away" of the ankle in the last 6 months, or feelings of ankle instability during sports or daily activities. Interventions: Digital cameras recorded movement while participants performed a single leg squat to 60 degrees and stepped off a 17 cm high step. Each task was repeated 3 times. Participants had markers on the following landmarks: anterior superior iliac spines, midshaft of the femur approximately two thirds proximal to the knee, tibial tuberosity, and centre of the malleoli. Digital images were imported into custom-built software and markers were used to calculate knee and pelvis angles. Main outcome measurements: Fontal plane knee and pelvis angles and amount of frontal plane movement during the tasks. Results: Knee and pelvic angles and amount of movement in the frontal plane did not differ between people with CAI and controls during single leg squat or step down tasks (p > 0.05). Conclusions: Frontal plane knee and pelvic kinematics are unaffected in CAI participants during functional tasks. Further research using motion analysis and increased task complexity should be used to confirm this finding and determine the need to address frontal plane knee and pelvis control in CAI management.